German Military Propaganda in the Battle of Stalingrad: Scale, Dynamics and Features - Oleg Romanko; Nikolay Smirnov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The study was based on a systematic approach. Historical-genetic and historicalcomparative methods were applied, as well as statistical methods, the synchronization method, and content analysis. The research was conducted using published materials and archival sources that allowed for an assessment of the scale of German propaganda against the Red Army during the Battle of Stalingrad and its effectiveness dynamics. Analysis. An examination of the main narratives used in German propaganda throughout the Battle of Stalingrad revealed changes in its directions and emphases over time. A review of Wehrmacht propagandists’ reports provided insights into their approaches to evaluating the effectiveness of their work, as well as the extent of their influence on units of the Red Army. The numbers of Soviet defectors and prisoners of war at different stages of the battle were determined, which served as the basis for assessing the effectiveness of German propaganda. Results. An examination of German propaganda methods during the Battle of Stalingrad revealed that the diversity of narratives decreased as the fighting for the city dragged on. Comparing the number of Soviet prisoners of war and defectors with the efforts expended showed a low effectiveness of German propaganda activities, with a consistent trend toward decline. Authors’ contribution. O.V. Romanko proposed the concept of the article, supervised the study, studied the historiography of the problem, and edited the final text of the work. N.A. Smirnov carried out analytical work on the analysis of sources, systematization, and classification of information about the organization and methods of the work of German propaganda in the Battle of Stalingrad, assessed its effectiveness based on calculated statistics, and designed the text of the article.